164k views
3 votes
If f(x) = x^2-2x-24 and g(x) = x^2-x-30, find (f-g)(x).

2 Answers

0 votes

Answer:

-x+6

Explanation:

if f(x) = x^2-2x-24 and g(x) = x^2-x-30, find (f-g)(x).

Do to this, you have to subtract equation g from equation f.

If you write it down and subtract them, your x^2 will cancel out and you will be left with -2x - (-x) and -24 - (-30). This will leave you with -x +6

User HannesBenson
by
4.8k points
4 votes

Answer:

Explanation:

(f-g)(x) = x² - 2x - 24 - (x² -x -30)

= x² - 2x - 24 -x² + x + 30

= x² - x² -2x + x - 24 + 30

= -x + 6

User Woodgnome
by
4.8k points